The Benefits Implications of Recent Trends in Flexible Staffing Arrangements - Susan N. Houseman (W.E. Upjohn Institute for Employment Research, 2001)
Workers in flexible staffing arrangements - including temporary agency, direct-hire temporary, on-call, and contract workers - are much less likely than regular, direct-hire employees to be covered by laws mandating or regulating workplace benefits. Workers in such arrangements, in turn, are much less likely to receive pension, health insurance, and other benefits on the job. This paper documents these differences in coverage by benefits regulations and differences in benefits receipt. The paper also reviews evidence on the incentives employers have to use workers in these various flexible staffing arrangements. Although reducing benefits costs is not the only reason employers use flexible staffing arrangements, it is an important factor motivating many employers to use them, and the level of and growth in these arrangements would be lower in the absence of this incentive.
Additional information: A revised version of this paper was published in Olivia S. Mitchell, David S. Blitzstein, Michael Gordon, and Judith F. Mazo, eds. Benefits for the Workplace of the Future. Philadelphia: University of Pennsylvania Press, 2003. Please cite the revised version.
Keywords: J3; J8; K3; 330; contingent; part-time; contract; benefits; pensions; health; Houseman